Implementation of Standard Operating Procedure: care in arterial catheterization in intensive care (Research, Society and Development, 2021)
The Standard Operating Procedure (SOP) is an instrument used to standardize nursing actions aiming at patient care security. The objective of the study is to design and implement a SOP in an Intensive Care Unit (ICU) on Invasive Blood Pressure (IBP), with the collaboration of the nursing department of the sector and the permanent education of the hospital. The study was carried out in a Hospital of the Federal Network of the city of Rio de Janeiro, located in the southern zone. This is an integrative review of the literature. For the elaboration and implementation of the SOP, relevant literature was used to promote the scientific basis and adaptation of the routine to the reality of the hospital after. As a result, the implementation of a new SOP in the sector was obtained, in order to standardize the nursing actions regarding the manipulation of the IBP, promoting a greater safety for the patient.